Pengembangan Media Pembelajaran Komik Materi Mengenal Nilai-Nilai Pancasila dan Bhineka Tunggal Ika untuk Siswa Kelas V di SDN 03 Tiumang - Susilawati, Wiwik Okta; Anggrayni, Melisa; Hasibuan, Rusdi Indra; putri, jatunina (Universitas Batanghari Jambi, 2024)
This study aims to develop a learning media to raise the enthusiasm of students in Pancasila Education subjects, grade V of SDN 03 Tumang. The researcher used comic learning media using the Canva application. The researcher used the type of Research and Development (R&D) development research, PLOMP, which has 3 stages, namely preliminary research, prototype development phase, and assessment phase. The types of data used are qualitative and quantitative data. 1). The validation of this comic learning media was assessed by 6 validators. Where the aspects assessed were question validation with a value of 78% in the valid category, question validation by the homeroom teacher with a value of 79%, language validation with a value of 95%, teaching module validation with a value of 77.5%, material validation 89.28%, and media validation 95.45%. Practicality was assessed by the homeroom teacher and students, 2). Effectiveness was assessed from student learning outcomes.